Synovial Fistula Associated With Total Knee Replacement Aseptic Loosening and Polyethylene Wear - Saul Hernandez-Rodriguez, MD, FAAOS; Liannette Padilla-Martinez, MLS, MD (Arthroplasty Today)
Synovial fistula of the knee occurs when a defect in the joint capsule creates a connection between skin, bursa, and a near tissue, manifesting as an opening with continuous draining fluid or a cyst. This is a case of an 80-year-old male who developed a synovial fistula with cystic presentation 6 years after the primary total knee arthroplasty. Management included a total knee arthroplasty revision surgery with intraoperative identification of the fistula with methylene blue, and using a gelatin-thrombin matrix for closure. This case shows a possible complication of catastrophic polyethylene insert wear and management.